Usługi biblioteczne w dobie cloud computing – technologia, dane, sieciowe, społeczności informacyjne - Firlej-Buzon, Aneta (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
This text refers to the application of cloud computing technology in modern libraries, with particular emphasis on large academic institutions. Based on the experiences of the Library of Congress, benefits from the use of cloud services by libraries and recommendations for the secure use of cloud technology. Networking of cloud-based information communities contributes to the growth of book and reader promotion, library support, and book development.